2008
DOI: 10.1111/j.1744-697x.2008.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium phytoextraction capacity in eight C3 herbage grass species

Abstract: Grasses are excellent candidates for phytoremediation because of their high biomass production, high adaptability and low management cost. This study assesses interspecific variation of cadmium (Cd) phytoextraction capabilities in eight C3 grass species. Populations of 30‐day‐old C3 grass species – namely, Agrostis alba, Anthoxanthum odoratum, Dactylis glomerata, Festuca arundinacea, Festuca pratensis, Lolium multiflorum, Lolium perenne and Poa pratensis– were grown hydroponically for 15 days with different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…When compared the two Lolium species, greater reduction in plant growth, due to spiked Cd in growth media, was observed in L. perenne than in L. multiflorum, suggesting that the latter has higher metal tolerance than the former. Similar reports were documented in Sabreen and Sugiyama (2008) who showed that L. perenne had a higher growth inhibition than L. multiflorum under Cd stress.…”
Section: Combined Effects Of CD Concentrations and Elevated Co 2 Levesupporting
confidence: 74%
See 1 more Smart Citation
“…When compared the two Lolium species, greater reduction in plant growth, due to spiked Cd in growth media, was observed in L. perenne than in L. multiflorum, suggesting that the latter has higher metal tolerance than the former. Similar reports were documented in Sabreen and Sugiyama (2008) who showed that L. perenne had a higher growth inhibition than L. multiflorum under Cd stress.…”
Section: Combined Effects Of CD Concentrations and Elevated Co 2 Levesupporting
confidence: 74%
“…They contain extensive root systems with high biomass, have high adaptability and low-cost management, and possess the ability to accumulate Cd (Sabreen and Sugiyama, 2008). Understanding the combined effects of elevated levels of CO 2 and metal contamination on their biomass productions, root morphological traits, and metal accumulations will improve both our knowledge of food safety and their survival abilities in metal contaminated environments.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of suitable plants to remediate heavy metal contaminated environments is the first limiting factor of phytoremediation. Due to phytoextraction plants yield a low biomass and grow relatively slowly, grass species are preferred for phytoremediation because their high biomasses and they have a fast growth rates and are easier to manage [51, 52]. Thus, it is economical to use them for phytoremediation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although phytoremediation efforts for the treatment of contaminated sites have a number of advantages over other traditional physical, chemical, or engineering approaches, soils contaminated with Cu, and other heavy metals can present a difficult challenge for this emerging technology . It was previously suggested that grass species can accumulate even more heavy metals than phytoaccumulators because they produce much higher levels of plant biomass; in addition, grasses tend to have lower associated costs and are easier to manage . Therefore, it is important to screen for plant species that are potentially suitable for phytoremediation, particularly at the field scale.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to screen for plant species that are potentially suitable for phytoremediation, particularly at the field scale. Due to the limitation of their biomass, difficult management, and high cost of using the already‐known Cu hyperaccumulators, the use of grass species or high‐biomass crops can be an even more efficient way to perform remediation .…”
Section: Introductionmentioning
confidence: 99%